Structural insights and biological activities of flavonoids: Implications for novel applications - Sheng Tang; Botao Wang; Xin Liu; Wenxia Xi; Yuanyuan Yue; Xiang Tan; Junying Bai; Linhua Huang (Food Frontiers)
Abstract Flavonoids are a major class of polyphenolic compounds that occur naturally in plants and are widely distributed in various dietary products. Flavonoids exhibit prominent physicochemical properties and biological activities, thereby garnering considerable attention. Notably, the physicochemical properties and functionalities of flavonoids are structurally dependent. Variations in chemical structure lead to differences in physicochemical characteristics among different flavonoid types. Structural alterations can modify these characteristics, influencing biological activities and mechanisms of action. However, these structural variations and their biological implication have not been comprehensively elucidated. In this review, we outline the structural characteristics of flavonoids, discuss biosynthesis, in vivo digestion, and absorption, and particularly emphasize the diverse biological activities and action mechanisms associated with different flavonoid structures. By summarizing the current scientific findings, we aim to elucidate the structure–activity relationships of flavonoids and provide a theoretical basis for the development of new flavonoid applications, which will help to target the design of functional molecules and moieties in the food and pharmaceutical industries for use in drug design and development. Practical Application: Understanding the structural characteristics and biological activities of flavonoids can guide the development of functional food products and dietary supplements with targeted health benefits. By leveraging the knowledge of flavonoid structure–activity relationships, food, and pharmaceutical industries can innovate formulations to enhance bioavailability and efficacy, potentially leading to the creation of tailored products for specific health conditions or dietary needs. This research lays the groundwork for the design of novel flavonoid‐based interventions aimed at promoting human health and well‐being.